Cytokinin response in pepper plants (Capsicum annuum L.) exposed to silver nanoparticles - Vinković, Tomislav; Novák, Ondrej; Strnad, Miroslav; Goessler, Walter; Jurašin, Darija Domazet; Parađiković, Nada; Vrček, Ivana Vinković (Environmental research, 2017)
The increasing development of different nanomaterials, such as silver nanoparticles (AgNPs), and their practical use in agriculture and biotechnology has created a strong need for elucidations of biological effects and risk assessments of AgNPs in plants. This study was aimed to investigate AgNPs effects on metal uptake and their biodistribution in pepper plants as well as on morphological parameters and hormonal responses of the isoprenoid cytokinin (CK) family. In addition, the comparison of effects silver form, nanoparticles vs. ionic, has also been examined. To the best of our knowledge, this is the first study describing CK responses in plants exposed to metallic NPs. The obtained results indicate that both AgNPs and Ag+ ions significantly increased total content of Ag+ in pepper tissues in a dose-dependent manner and affected on plant development by decreasing both plant height and biomass in a similar way. This study evidenced for the first time the role of CKs in abiotic stress in plants caused by AgNPs. The hormonal analysis, conducted by an ultra-high performance liquid chromatography-electrospray tandem mass spectrometry, revealed a significant increase in total CKs in the leaves and also highlighted the importance of cis-zeatin type CKs in plants treated with AgNPs. Our observations suggest potential risks of AgNPs on plant ecosystems upon their release into the environment.
Keywords: Uptake; Cytokinins; Capsicum; Abiotic stress; Silver; Biodistribution; Cytokinin response; stříbro; Pepper; kovové nanočástice; Metal Nanoparticles; Silver nanoparticles; cytokininy